ANALISIS PENGARUH VARIASI CDI DAN BUSI TERHADAP PERFORMA DAN KONSUMSI BAHAN BAKAR PADA MOTOR VESPA STRADA - Riyadi; Nugroho Gama Yoga; Muhammad Lutfhi Aziz (Universitas Negeri Jakarta, 2023)
In current developments, CDI ignition systems are widely used in motorcycle vehicles. This study aims to determine the effect of using variations of CDI Limiter and CDI unlimiter with spark plugs on torque, power, and fuel consumption using pertamax fuel. The research method is an experimental research method, carried out on a Vespa Strada 150 CC motorcycle. Research data obtained from tests using a dynamometer to determine the value of torque and power generated which will later be analyzed by directly observing the experimental results then drawing conclusions and determining the results of research conducted in the form of tables and diagrams, while for testing fuel consumption using measuring cup and calculating fuel consumption. Based on this report, shows that there are differences in torque, power, and fuel consumption produced. The highest torque value is found in the CDI unlimiter variation with platinum spark plugs at a rotating speed of 11000 rpm producing a torque of 7.09 Nm, while the highest power value is also found in the CDI unlimiter variation with Platinum Spark Plugs at 11000 rpm of rotating speed producing power of 10.7 HP and fuel consumption (SFC) the highest value was obtained in the CDI Limiter variation with platinum spark plugs at 11000 rpm resulting in an SFC of 0.67 L/HP.h.